2009
DOI: 10.1007/s00277-008-0688-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to glycosylphosphatidyl-inositol anchored proteins (GPI-AP) in antithymocyte and antilymphocyte globulin: possible role for the expansion of GPI-AP deficient cells in aplastic anemia

Abstract: Antithymocyte globulin (ATG) and antilymphocyte globulin (ALG) are currently used successfully for immunosuppressive treatment of aplastic anemia. In this study we have investigated whether commercial ATG/ALG preparations contain antibodies against glycosylphosphatidyl-inositol anchored proteins (GPI-AP), which could be responsible for emergence of GPI-deficient populations in aplastic anemia after ATG/ALG therapy. We analyzed four commercial ATG/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…As a result, the relative concentrations of antibodies recognizing various antigens expressed on T-cells vary between ATG-GENZ and ATG-FRES. For example, ATG-GENZ contains more antibodies recognizing CD8, CD11a, CD18, CD44, CD52, CD99 while ATG-FRES recognizes more CD5, CD98, and CD147 (5, 40), although other studies reported different antigens (41, 42).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the relative concentrations of antibodies recognizing various antigens expressed on T-cells vary between ATG-GENZ and ATG-FRES. For example, ATG-GENZ contains more antibodies recognizing CD8, CD11a, CD18, CD44, CD52, CD99 while ATG-FRES recognizes more CD5, CD98, and CD147 (5, 40), although other studies reported different antigens (41, 42).…”
Section: Discussionmentioning
confidence: 99%
“…While studies in both primates and humans have shown that rATG does deplete T cells 1, 2, several other studies have identified rATG antibodies that might prevent injury due not only to rejection but also to inflammation associated with brain death and/or reperfusion 3, 4, 5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…Although rATG was developed as an agent to deplete T cells, its manufacture results in the generation of multiple antibodies against a myriad of distinct epitopes. While studies in both primates and humans have shown that rATG does deplete T cells (1,2), several other studies have identified rATG antibodies that might prevent injury due not only to rejection but also to inflammation associated with brain death and/or reperfusion (3)(4)(5)(6). and with cardiopulmonary instability, the prescribing information for rATG (in treating kidney rejection) recommends administering a series of small doses spaced at 1-or 2-day intervals (divided-dose rATG [DD-rATG]), along with premedication that includes corticosteroids (7).…”
mentioning
confidence: 99%